SENJATA PEMUSNAH MASSAL DAN MASA DEPAN KEAMANAN INTERNASIONAL - Adi Joko Purwanto (Universitas Wahid Hasyim Semarang, 2011)
Abstract This article tries to explore the dynamics of international security, especially the ownership of weapons mass destruction (WMD). Recently the issue of weapons mass destruction remains a critical issue in international security. Many countries around the world use nuclear power as a powerful weapon for deterrence and defense from possible enemy attack, nuclear also able to serve as bargaining position, and Taking profits in other fields (eg. economics and politics). Yet the ownership of weapons of mass destruction turned out to leave the problems. one of them is the future of international security. Keywords: international security, weapons of mass destruction, nuclear proliferation, the balance of power, nuclear diplomacy.